Merger simulation in competition policy: a survey - Oliver Budzinski; Isabel Ruhmer (Philipps-University Marburg, Faculty of Business Administration and Economics, 2008)
Advances in competition economics as well as in computational and empirical methods have offered the scope for the employment of merger simulation models in merger control procedures during the past almost 15 years. Merger simulation is, nevertheless, still a very young and innovative instrument of antitrust and, therefore, its technical potential is far from being comprehensively exploited and teething problems in its practical use in the antitrust environment prevail. We provide a classification of state-of-the-art merger simulation models and review their previous employment in merger cases as well as the problems and limitations currently associated with their use in merger control. In summary, merger simulation models represent an important and valuable extension of the toolbox of merger policy. However, they do not qualify as a magic bullet and must be combined with other, more traditional instruments of competition policy in order to comprehensively unfold its beneficial effects.
Keywords: L40; C15; K21; 330; merger simulation; merger control; antitrust; oligopoly theory; auction models; mergers & acquisitions